Some Aspect in Different Modalities of Management of Placenta Accreta Spectrum at Al-Elwiya Maternity Teaching Hospital - AbdUlAmeer, Mays Mustafa; Sarsum, Samar Dawood (Journal of Science in Medicine and Life, 2025)
Background: Placenta accreta spectrum is one of the most dangerous conditions associated with pregnancy, because hemorrhage may result in multisystem organ failure, disseminated intravascular coagulation, need for admission to an intensive care unit, hysterectomy, and even death. The antenatal diagnosis of placenta accreta spectrum is critical because it provides an opportunity to optimize management and outcomes. Cesarean hysterectomy is considered the gold standard treatment for invasive accreta but it remains associated with high rates (40%–50%) of severe maternal morbidity and, in cases of placenta percreta, Aim of the study: To highlight on the modalities of managing patients with PAS and maternal outcome accordingly at Elwiya hospital. Patients and methods: This is a prospective cohort study conducted at the Department of Obstetrics and Gynecology Elwiya Maternity Teaching Hospital during a period extended from 1st of January 2022 to 1st of October 2022. The study included all cases of PAS presented to our hospital during this period. Interpretation of indication and outcome of both hysterectomy and uterine conserving surgery were compared. Results: The study included 30 participants who had preoperative diagnosis of placenta accreta spectrum by ultrasound or intraoperative diagnosis. According to the type of management the studied sample divided into two groups, hysterectomy group included 21 cases and uterine conserving surgery was done in 9 cases. The two groups were not different regarding demographic data, previous medical and surgical histories, and presentation. Regarding the outcome of the surgery, cases of hysterectomy had significantly higher rate of bladder injury and bowel injury, higher amount of blood transfusion, longer duration of the surgery and longer hospital stay than uterine conserving surgery. Conclusion: Uterine conserving surgery is associated with lower rate of bladder injury, lower requirement of blood transfusion, shorter operative time and hospital stay.